Network relationship marketing strategy for The success of micro, small and medium Enterprises in sri lanka - Sathana, V. (University of Colombo, 2021)
MSMEs have been facing huge problems and challenges to sustain their business in the challenging environment in Sri Lanka. Network relationship marketing is a unique strategy to take a competitive advantage in the challenging environment and change marketing activities. Little efforts are enforced to understand the network relationship marketing for MSMEs in Sri Lanka. This research explores the dimensions of network relationship marketing strategy in MSMEs, which serve as decisive dimensions for developing network relationships in the MSME market. This research applied qualitative methodology. Data were obtained by interviewing owners of MSMEs in Sri Lanka. The coding method was applied to identify the dimensions of the network relationship marketing strategy. Three major dimensions were produced for network relationship marketing: intensive network relationship marketing, business network relationship marketing, and social network relationship marketing strategy. The dimensions of intensive network relationship marketing strategy are network relationships with customers, distributors, suppliers, employees, and competitors. Business network relationship marketing includes the network relationship with government institutions, intermediary institutions, and research institutions. Social network relationship marketing dimensions are a marketing tool, communication convergence, and power to influence. The vital part of the research is to produce new theories and dimensions of variables of network relationship marketing strategy for MSMEs. Indeed, this research revealed that network relationship marketing practices help MSMEs to manage competitive nature in a dynamic environment. This study adapted the network relationship marketing strategy as an intangible resource to take advantage of MSMSS MSMEs. The finding of the research represented and generalised to the MSMEs in the developing countries.
Keywords: Network relationship marketing strategy; MSMEs; Intensive network relationship marketing; Business network relationship marketing; Social network relationship marketing